A synthesis of the Chiococceae tribe (Cinchonoideae, Rubiaceae) in Mexico: morphology, diversity, and endemism - Torres-Montufar, Alejandro; Sanchez-Bautista, Saray; Aguilar-Morales, María (Phytotaxa, 2022)
This study provides the first comprehensive checklist and analysis of species included in the Chiococceae tribe in Mexico, based on over 4000 herbarium specimens. We report 28 species in nine genera; including two endemic genera (Coutaportla and Nernstia) and 14 endemic species. It is estimated that 50 % of Chiococceae species found in Mexico are endemic. We mapped the diversity per grid cell of species using their occurrence records obtained from online databases. Distribution was concentrated in the tropical southern area of Mexico, with the most diverse states in terms of species and endemicity being Chiapas (17 species; 5 endemic), Veracruz (14 species; 4 endemic), and Oaxaca (14 species; 6 endemic). The combination of several traits in reproductive characters are useful to diagnose the generic entities of Chiococceae; for example form, size, symmetry, and merosity of the corolla; consistency, dorsiventral compression, and dehiscence of the fruit; and attachment and margin of the seed are useful for diagnosing the generic entities of Chiococceae. We also highlight taxonomic problems on the generic level (Asemnantha/Chiococca, Coutaportla/Lorencea; Solenandra/Exostema) and species level (e.g. Chiococca alba), for which further studies are needed to better comprehend the diversity of the Chiococceae tribe in Mexico.